The potential roles of outdoor water features in the mosque - Mohd Shabri, Nurul Syuhadah; Zakariya, Khalilah (KAED, IIUM, 2016)
Water is a pivotal element in the human civilizations. The use of outdoor water features in people’s daily life can be traced back to the history and geography of places. In landscape architecture, water plays a vital in the design of public spaces. Likewise, in the compound of the mosque, outdoor water features are designed to resemble the water flowing in Jannah. This paper examines the types and multiple functions of outdoor water features in the mosque that can benefit towards environmental, physical, social and religion aspects. Hence, this paper discusses the potential roles of outdoor water features that not only functions as a decorative element. It is also encouraged in Islam to optimize the functions of water at the mosque in order to reduce water wastage. A case study method was conducted involving site observation and semi-structured interview to collect the data. The result indicated that water from outdoor water features can be used for other purposes such as water for cleansing, drinks for animal and ablution. Besides, the water feature is also used to cool the space naturally. This finding is useful to landscape architects and designers to improve the functionality and design of outdoor water features in the mosques as a sacred place.